Histological changes of the periodontal ligament and alveolar bone in front to light orthodontic forces (pilot study) - Soldevilla Galarza, Luciano (2005)
The maxillary bone the same as the periodontal ligament experiences constant changes when light forces are used, however, they are persistent during the orthodontic treatments. The tooth is treated as body deformable that separates the periodontal ligament and of the bone. The formation and bony resorption happen in a continuous way, but a physiologic balance exists between both. Under normal conditions, the bone suffers constant resorption and in other the regular state of that moment is conserved. The physiologic state of the bone depends on the age and its functions. It is cIear that the speed of resorption and bone apposition will depend on the answer settled down by the function; however, during the movement dentario through the bone for orthodontic forces, Ule thickness of the ligament remains in a constant value.